What are the basic substances of the universe? Current research and future predictions - Y Liu (My University, 2025)
Exploring the fundamental components of the universe remains one of the most profound challenges in science. Although significant progress has been made in terms of particles and forces, the composition of the universe is far from being solved. This article explores the hypothesis that the most basic matter in the universe is composed of four interrelated elements: matter, energy, time and space. We believe that these components are not only the basis of physical phenomena, but also the basic components of atoms and the universe. This article describes the advantages and limitations of established theories such as Standard Model and General Relativity, and draws evidence from cosmology, quantum mechanics, and particle physics, and conducts in-depth research on the complex relationships of matter, energy, time and space on different scales. By proposing the overall framework for the interaction of these four elements, we raise the need for future physics research to unify the microscopic and macroscopic worlds and explore other long-standing major issues in physics.